Bioacoustic description of the alarm call of the stump-tailed porcupine (Coendou rufescens) - Batallas, Diego; Brito, Jorge (Therya Notes, 2022)
Acoustic communication in rodents is complex and varied. However, bioacoustic studies of rodents in the wild are limited and scarce, most are performed, under controlled laboratory conditions. We recorded the alarm call of the short-tailed porcupine in the wild for the first time. Recordings were obtained in Guabisai, Sangay National Park, Ecuador. We opportunistically recorded the alarm call of an adult female Coendou rufescens in a direct encounter during its capture process. We analyzed 37 notes of 21 calls, categorizing the notes into 4 different types based on their spectral, temporal, and intensity characteristics (i.e., fundamental, dominant and harmonic frequencies). The alarm call of C. rufescens consists of up to 4 notes. The sounds vary, ranging from chirps to nasal sounds, with the dominant frequency ranging from 0.34-2.50 kHz. The notes have different spectral and temporal characteristics. Therefore, the alarm call of C. rufescens presents a repertoire with different types of notes. Our preliminary observations suggest that their different types of sound are probably associated with anti-predatory behaviors, therefore we considered these sounds as alarm calls. This report provides baseline information for future bioacoustic studies on this species.